Beyond sport to combat childhood obesity: educating, engaging, and preventing through an integrated school-based campaign grounded in the values of Olympism - Zuccotti, Gianvincenzo; Ascani, Franco Bruno; Romeo, Assunta Ferdinanda; Calcaterra, Valeria; , PODiaCar Team (Frontiers in Endocrinology, 2025)
IntroductionPromoting sports in schools is a key strategy to address childhood obesity and raise awareness of the benefits of physical activity. The “Trofei di Milano Cortina 2026” initiative, in collaboration with Buzzi Children’s Hospital in Milan, launched a comprehensive school-based campaign to promote Olympism and healthy lifestyles.MethodsThe initiative involved 350 schools across primary and lower secondary levels, offering free educational and sports activities in two phases: a year-long educational component followed by a final sports event. Educational materials, including an animated cartoon “Grandma Wilma’s Tales,” supported the EU-backed project on combating pediatric obesity and educating children on diabetes and cardiovascular risk.ResultsOut of the targeted schools, 95 (27.1%) formally joined, involving 2.100 classes and 51.066 students aged 6 to 13. Participation in educational activities was substantial, with thousands of modules completed across five thematic areas, such as “Sport in a Video,” “Sustainability Champion,” and “Education 4.0.” The initiative engaged 312 teachers and included hospital school participation. The sporting phase registered 8,658 participants, nearly evenly split by gender. A network of 10 public and sports institutions, along with two sponsors, supported the program, highlighting the initiative’s wide-reaching impact and collaborative strength in fostering youth health and well-being.ConclusionsThe data confirm the initiative’s success, highlighting strong community engagement and broad acceptance of the educational model. Integrating sport, values, and education proves to be an effective, scalable strategy for positively and collectively preventing childhood obesity.